La silueta de la inteligencia artificial (2020)
This project is made out of a series of fashion illustrations in collaboration with the results of an artificial intelligence model. With the goal of understanding how the use of artificial intelligence can enhance creativity during the design process in fashion, furthermore, this project wants to observe the differences between humans and machines perception in regards to gender in clothing.